Designing the Healthy Eating and Active Lifestyles for Diabetes (HEAL-D) self-management and support programme for UK African and Caribbean communities: a culturally tailored, complex intervention under-pinned by behaviour change theory - Amanda P. Moore; Carol A. Rivas; Stephanie Stanton-Fay; Seeromanie Harding; Louise M. Goff (BMC, 2019)
Abstract Background UK African and Caribbean (AfC) communities are disproportionately burdened by type 2 diabetes (T2D). Promoting healthy eating and physical activity through structured education is the cornerstone of T2D care, however cultural barriers may limit engagement in these communities. In addition, changes in lifestyle behaviour are shaped by normative influences within social groups and contextual factors need to be understood to facilitate healthful behaviour change. The Behaviour Change Wheel (BCW) and associated COM-B framework offer intervention designers a systematic approach to developing interventions. The aim of this study was to apply the BCW in the design of a culturally sensitive self-management support programme for T2D in UK AfC communities. Methods An intervention development study was conducted. Focus groups were held with 41 AfC patients with T2D to understand healthful weight-management, diet and physical activity behaviours. The COM-B framework and BCW were used to evaluate the qualitative data, identify appropriate behaviour change techniques and specify the intervention components. Results Participants were motivated to avoid diabetes-related consequences although did not always understand the negative impact of their current health behaviours on long-term diabetes outcomes. Barriers to healthful behaviour included gaps in knowledge related to diet, physical activity and weight management guidance. In addition, motivation and social opportunity barriers included an acceptance of larger body sizes, rejection of body mass index for weight guidance and cultural identity being strongly linked to consumption of traditional starches. There was a lack of social opportunity to perform moderate to vigorous physical activity, although walking and dance were culturally acceptable. The resulting Healthy Eating & Active Lifestyles for Diabetes (HEAL-D) intervention uses social support, social comparison, credible sources and demonstration as key behaviour change techniques. Conclusion Use of COM-B and the BCW highlighted the need for an intervention to address motivational and social opportunity barriers to engaging in healthful behaviours, as well as addressing key gaps in knowledge. This framework facilitated the linkage of theoretical behaviour constructs with evidence-based behaviour change techniques, which will enable us to evaluate operationalisation of our chosen BCTs and their impact on behaviour change in a future feasibility study.